Flow cytometric analysis of the immune cell subsets in adult hemophagocytic lymphohistiocytosis - Qin, Yao; Zhou, Jianying; Liu, Pengpeng; Dai, Yang; Tang, Yun; Zhong, Xushu; Chen, Xinchuan; Zhu, Huanling; Liu, Ting (Frontiers in Immunology, 2025)
PurposeHemophagocytic lymphohistiocytosis (HLH) is a hyperinflammatory syndrome characterized by the dysfunction of cytotoxic T cells (CTLs) and natural killer (NK) cells. The status of these immune cells during persistent inflammation remains unclear. This study aimed to investigate the immune cell subsets, the exhaustion and activation status, and the cytotoxic functions of the CTLs and NK cells in adult HLH. Furthermore, the features of immune cells in patients with Epstein–Barr virus-associated HLH (EBV-HLH) before and after treatment with programmed death-1 (PD-1) inhibitors were also analyzed.MethodsFlow cytometry was utilized to evaluate the immune cell features in 75 patients with adult HLH.ResultsThis study observed skewed immune cell subsets, along with substantial exhaustion and activation in patients with adult HLH. Significant decreases were noted in NK, natural killer T (NKT), regulatory T cells (Tregs), CD4+ central memory T (TCM), CD8+ terminal effector memory T (TEMRA), and CD56dimCD16+ NK cells, while increases were found in the CD56brightCD16− and CD56dimCD16− NK subsets. The exhaustion markers (PD-1, TIGIT, and PD-L1) were elevated in CD8+ T cells and NK cells, and the activation markers (CD69, HLA-DR, and CD163) were higher in monocytes. An impaired IFN-γ production and a reduced degranulation function were also detected in CD8+ T cells and NK cells. In EBV-HLH patients treated with PD-1 inhibitors, we observed an increase in cytotoxic CD8+ T cells and CD56dimCD16+ NK cells and a decrease in CD56brightCD16− NK cells.ConclusionThese findings suggest impairments in cytotoxic immune cells along with a widespread immune exhaustion and an aberrant activation in adult HLH. The results also indicate potential differentiation defects in CD8+ T cells and NK cells. Treatment with a PD-1 inhibitor may contribute to partial functional recovery and support viral clearance in EBV-HLH, which warrant further investigation.